Nintedanib in Rheumatoid Arthritis-Related Interstitial Lung Disease: Real-World Safety Profile and Risk of Side Effects and Discontinuation - Sebastiani, Marco; Lepri, Gemma; Iannone, Claudia; Cassione, Emanuele Bozzalla; Guggino, Giuliana; Lo Monaco, Andrea; Foti, Roberta; Fornaro, Marco; Chimenti, Maria Sole; Fassio, Angelo; Truglia, Simona; Cozzini, Francesca; et al. (Journal of rheumatology, 2025)
Some concerns remain about the safety of nintedanib in patients with rheumatoid arthritis-related interstitial lung disease (RA-ILD), such as in the presence of comorbidities or in combination with biologic, targeted synthetic, and/or conventional synthetic disease-modifying antirheumatic drugs (DMARDs). In this multicenter study, we retrospectively evaluated the safety of nintedanib in a real-world population of patients with RA-ILD from the Italian Group for the Study of Early Arthritis (GISEA) registry and the possible role of comorbidities and DMARDs on drug safety and withdrawal. Our secondary aim was to investigate the causes of nintedanib discontinuation. Sixty-five patients treated with nintedanib in accordance with the current therapeutic indications were enrolled in the study. Nintedanib was prescribed in combination with DMARDs and/or steroids in 62 patients (95.4%). The 12-month retention rate of nintedanib was 76.7% and the drug was effective in about 80% of patients with ≥ 6 months of follow-up. Adverse events (AEs) were recorded in 36 subjects (55.3%), and these were mainly gastroenteric. Thirty-one subjects required a reduction of the nintedanib dose; among them, a transient or permanent reduction of the daily dose of nintedanib allowed the continuation of the treatment in 22, whereas 15 (23.1%) withdrew from the drug. All reductions and discontinuations were owing to treatment-related AEs. Comorbidities were significantly associated with side effects in multivariate analysis, whereas AEs due to nintedanib were the main cause of discontinuation. Combination therapy with DMARDs did not reduce the safety and effectiveness of nintedanib, and AEs were the main cause of drug withdrawal or dose reduction, mainly owing to comorbidities.